Step-by-step explanation:
3 answer.....
......dkdkdk
Answer:
See below, please!
Step-by-step explanation:
To multiply a whole number by a fraction, set up both numbers so that they have a numerator and denominator, multiply the corresponding parts, and simplify.
Ex:
. Both of them are in fraction form, right? Now multiply the numerator and denominator together. Doing this, you get 16/6. Now simplify. Look for a common factor between both the numerator and denominator. We can see that one common factor is 2. So, our simplified fraction is 8/3.
Hope this helped!
Combining the like terms, the simplified polynomials are given as follows:
a) 4x² - 14x + 17
b) -5x² - 20x + 8
<h3>How are polynomials simplified?</h3>
Polynomials are simplified combining the like terms, that is, adding these numbers with the same variable.
Item a:
4(x - 2)(x + 1) - 5(2x - 5)
Applying the distributive property:
4(x² - x - 2) - 10x + 25
4x² - 4x - 8 - 10x + 25
Combining the like terms:
4x² - 4x - 10x - 8 + 25
4x² - 14x + 17
Item b:
-5(x + 2)² + 28
-5(x² + 4x + 4) + 28
-5x² - 20x - 20 + 28
-5x² - 20x + 8
More can be learned about the simplification of polynomials at brainly.com/question/24450834
#SPJ1
Answer:
vvvvvcvv
Step-by-step explanation:
Answer:
(x - 3)² - 16 = 0
Step-by-step explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
Subtract 7 from both sides
x² - 6x + 7 = 0 ← in standard form
with a = 1, b = - 6
Given a quadratic in standard form then the x- coordinate of the vertex is
= -
= -
= 3
Substitute x = 3 into the equation for y
y = 3² - 6(3) - 7 = 9 - 18 - 7 = - 16 ⇒ (h, k) = (3, - 16)
y = (x - 3)² - 16 = 0